Transdisciplinarity: Theory and Practice - Nicolescu, Basarab 1942- (Cresskill, NJ Hampton Press, 2008)
In this fascinating volume, the contributors make it very clear that far from being a faddish and superficial phenomenon, transdisciplinarity is potentially the foundation for a new, and much needed approach to inquiry. Because transdisciplinarity is radical, in the sense that it goes to the roots of knowledge, and questions our ways of thinking and our construction and organization of knowledge, it requires a discipline of self-inquiry that integrates the knower in the process of knowing.
Keywords: Social science